Increasing wheat yield through frontline demonstration in Pali district of Rajasthan - Meena, Moti Lal; Singh, Dheeraj (Journal of Cereal Research, 2018)
Wheat (Triticum aestivum L.) is a major cereal crop of rabi season in Pali district of Rajasthan. However, its productivity is very low as compared to other districts. The Krishi Vigyan Kendra Pali has carried out frontline demonstrations (FLDs) on wheat covering an area of 124 ha of farmers fields from 2009-10 to 2015-16 to exhibit latest production technologies and compared it with farmer’s practice. An attempt has also been made to know the increased productivity and economics of front line demonstrations and the adoption of latest production technologies by the 120 FLD farmers and 120 non-FLD farmers. FLD farmers and non-FLD farmers were randomly selected from FLD villages. The results revealedthat improved technologies enhanced wheat yield from 42.09 q/ha to 49.5q/ha in front line demonstrations. The percentage of increase in yield ranges from 25.1 to 38.4. The economic analysis of yield performance showed that front line demonstrations recorded higher average gross return (Rs.70563/ha), higher average net return (Rs. 46677/ha) with higher cost benefit ratio of 3.0 as compared to local check. Full extent of adoption of improved technologies of wheat cultivation ranged from 28.33 to 95.83% FLD farmers while it was in the range of 5.83 to 55.0% in case of non-FLD farmers. This might be due to adotption of improved production techologies of wheat demonstration under FLD has led to better yield and income. Doi.org/10.25174/2249-4065/2018/76657